Microbial decomposition of biodegradable plastics on the deep-sea floor - Taku Omura; Noriyuki Isobe; Takamasa Miura; Shun’ichi Ishii; Mihoko Mori; Yoshiyuki Ishitani; Satoshi Kimura; Kohei Hidaka; Katsuya Komiyama; Miwa Suzuki; Ken-ichi Kasuya; Hidetaka Nomaki; et al. (Nature Communications, 2024)
Abstract Microbes can decompose biodegradable plastics on land, rivers and seashore. However, it is unclear whether deep-sea microbes can degrade biodegradable plastics in the extreme environmental conditions of the seafloor. Here, we report microbial decomposition of representative biodegradable plastics (polyhydroxyalkanoates, biodegradable polyesters, and polysaccharide esters) at diverse deep-sea floor locations ranging in depth from 757 to 5552 m. The degradation of samples was evaluated in terms of weight loss, reduction in material thickness, and surface morphological changes. Poly(l-lactic acid) did not degrade at either shore or deep-sea sites, while other biodegradable polyesters, polyhydroxyalkanoates, and polysaccharide esters were degraded. The rate of degradation slowed with water depth. We analysed the plastic-associated microbial communities by 16S rRNA gene amplicon sequencing and metagenomics. Several dominant microorganisms carried genes potentially encoding plastic-degrading enzymes such as polyhydroxyalkanoate depolymerases and cutinases/polyesterases. Analysis of available metagenomic datasets indicated that these microorganisms are present in other deep-sea locations. Our results confirm that biodegradable plastics can be degraded by the action of microorganisms on the deep-sea floor, although with much less efficiency than in coastal settings.